Analisis Pengaruh Risiko Bisnis, Likuiditas, Pertumbuhan Perusahaan, Dan Struktur Aset Terhadap Struktur Modal Perusahaan - Zaen, Muhammad Afrizal; Aris, Muhammad Abdul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Capital structure is used as a measuring tool to determine the ideal capital structure and is one type of information that is important to consider in decision making. This study aims to determine whether business risk, liquidity, company growth, and asset structure affect the capital structure. The approach used in the study is quantitative research. The data measured is by a numerical scale that can be examined using statistical analysis. The sample of this study is 41 mining sector companies listed on the Indonesia Stock Exchange.Sampling technique using purposive sampling technique. The sample obtained from 2020-2022 amounted to 41 companies with. The method of data analysis used in this study is an analytical tool used by researchers in the form of descriptive statistical analysis, classical assumption test, multiple linear regression test and hypothesis test using SPSS version 25.0. The results provide evidence that business risk, liquidity, and asset structure have a negative and significant effect on capital structure. While the company's growth does not affect the capital structure.